(20S)-20-Acetoxy-4-pregnene-3,16-dione from Commiphora wightii - Yousuf, S.; Ahmed, R.; Ali, Z.; Choudhary, M.I.; Ng, S.W. (International Union of Crystallography, 2010)
The title triterpene compound, C23H32O4, isolated from Commiphora wightii features four trans-fused rings, among which the five-membered ring adopts an envelope conformation, the cyclohexene ring adopts a half-chair conformation and the two cyclohexane rings exist in chair conformations. The asymmetric unit contains two independent molecules. Weak intermolecular C-H center dot center dot center dot O hydrogen bonding is present in the crystal structure.